EVALUATING PERFORMANCE TO IMPROVE CAPACITY EFFECTIVITY AND TIME OF SERVICE: STUDY CASE PT BERKAH MULTI CARGO (The Indonesian Journal of Business Administration, 2019)
This paper aims to evaluate design layout depot container to improve the performance of existing capacity to be more efficient. The design of the layout depot container can now be said to have not followed a good design so that it needs to change the container depot design as a whole so that the existing capacity in each depot can be maximized.Data collection is a very important method in a study. Data collection in this study through field observations for 7 days at 09.00-16.00 where at this hour were the busiest and active hours in each depo. As for historical data, it will use production data from Depo CCC-CDC for 2015 to 2018. Where this data includes container flow data that goes to the Banjarmasin CCC-CDC depot.Based on the results of interviews that have been conducted, many say that the container service time is long because the position of the container is piled up by another container, so it is necessary to shift the container first. Shifting containers vary from 1 box to 3 boxes. With this container shifting, it can be concluded that container arrangement still needs to be improved and the costs that come out become bigger.The effect of fuel consumption greatly affects the cost because the price for subsidized Solar fuel is Rp 5.150.00 and Solar Industry is Rp 11,020.00. With a better arrangement on the container, depot can reduce shifting containers will affect the cost of Reach Stacker because the costs incurred by Reach Stacker is quite large. Truck costs will also decrease because the fuel consumption will also decrease because trucks will be served faster and require less time in the container depot. Reduce waiting times for service and control of parking vehicles in the container stacking area.Keywords:  Capacity, Container, Depot Container, Layout, Shifting